Realistic architectural visualization with 3ds Max and mental ray. - Cusson, Roger, ....-; Cardoso, Jamie, ....- (Amsterdam : Elsevier, 2010)
Revitalize your architectural visualizations by bringing new levels of realism to them with an enhanced command of the mental ray toolset in 3ds Max. Full-color step-by-step tutorials give you a firm understanding of the processes and techniques needed to create impressive interior and exterior visualizations. You'll learn how to prepare materials, light a daytime interior scene, use mr Physical Sky, and how to save time during complex renders. The companion website includes all of the tutorial files and sample files from the book. Plus find more information at http://jamiecardoso-mentalray.blogspot.com/. * Beautiful full-color visualization projects provide step-by-step instruction on valuable techniques and tools * An official Autodesk Techniques co-branded title written by an authoritative expert on visualization * Companion website contains all of the tutorial files from the book